Preferensi Konsumen terhadap Mangga Putar Pasuruan: Implementasi Discrete Choice Experiment terhadap Atribut Produk dan Willingness to Pay - Maghrobi, Aghitsni Aulia; Sunaryono, Joko Gagung; Sule, Suryaman (Universitas Galuh, 2025)
Mangga Putar Pasuruan is one of the distinctive varieties from Pasuruan, East Java, which has significant economic potential and cultivation value. However, this horticultural product has not yet been maximally optimized in its marketing strategy. This research aims to analyze consumer preferences for Pasuruan Spin Mango, focusing on several attributes prioritized by consumers such as taste, size, packaging, and price. The purpose of this research is: 1) Identifying the characteristics of Mangga Putar Pasuruan consumers, 2) Analyzing consumer preferences for Mangga Pasuruan attributes, and 3) Analyzing the marginal Willingness to Pay for Mangga Putar Pasuruan. The descriptive quantitative study using the Discrete Choice Experiment (DCE) approach is the method employed in this research. Non-probability sampling with random or accidental sampling techniques was used to determine the research sample. This research was conducted online through a questionnaire distributed on social media with the criteria that respondents had previously consumed Mangga Putar Pasuruan. The number of respondents collected was 239 respondents. The research results show that respondents prefer attributes such as sweet taste, medium size, large cardboard packaging, and an affordable price of IDR 10,000. Meanwhile, the sociodemographic aspect produced several attribute combinations that matched the characteristics of each respondent. Additionally, the attribute of sweetness has a high value in the marginal Willingness to Pay results. From the results of this study, farmers or producers of Mangga Putar Pasuruan need to develop market-oriented marketing strategies by adjusting production and distribution of products based on the attributes most favored by consumers.